Festival Mangga sebagai Media Komunikasi dalam Mengoptimalkan Daya Tarik Wisata Desa Penggarit - Himawan Ardhi Ristanto; Adhi Iman Sulaiman; Shinta Prastyanti (Program Studi Ilmu Komunikasi FBIK Unissula, 2023)
Various tourism potentials exist in Penggarit Village, such as agricultural, religious, cultural, and natural educational tours. Mango has become the identity of Penggarit Village. Because this village is a producer of mangoes with the branding